2008
DOI: 10.3892/ijo.32.3.545
|View full text |Cite
|
Sign up to set email alerts
|

YM753, a novel histone deacetylase inhibitor, exhibits antitumor activity with selective, sustained accumulation of acetylated histones in tumors in the WiDr xenograft model

Abstract: Histone deacetylase (HDAC) inhibitors have been shown to have antitumor activity in vitro and in vivo. Various studies related to their antitumor activity and mechanism of action have been reported for HDAC inhibitors, but the relationship of their antitumor effects to their pharmacodynamic and pharmacokinetic properties in vivo has not ever fully characterized. We report here the discovery of a novel cyclic-peptide-based HDAC inhibitor, YM753. YM753 is a bacteria-derived natural product containing a disulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…We identified OBP-801, also known as YM753, as a novel HDAC inhibitor with attractive pharmacodynamic and pharmacokinetic properties by screening for a p21 WAF1/Cip1 -inducing agent (9). OBP-801 exerted the most potent HDAC-inhibitory activity tested; it was about 50 times more effective than SAHA, the most clinically used HDAC inhibitor (9).…”
Section: Introductionmentioning
confidence: 99%
“…We identified OBP-801, also known as YM753, as a novel HDAC inhibitor with attractive pharmacodynamic and pharmacokinetic properties by screening for a p21 WAF1/Cip1 -inducing agent (9). OBP-801 exerted the most potent HDAC-inhibitory activity tested; it was about 50 times more effective than SAHA, the most clinically used HDAC inhibitor (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that HDAC inhibitors synergize with cisplatin (8) or gemcitabine (9) and could potentially increase clinical efficacy in bladder cancer (10). We previously reported that OBP-801/ YM753, identified as a novel HDAC inhibitor by screening for p21 WAF1/Cip1 -inducing agents, had attractive pharmacodynamic and pharmacokinetic properties (11). OBP-801 exerted the most potent HDAC-inhibitory activity when compared with other HDAC inhibitors (11).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that OBP-801/ YM753, identified as a novel HDAC inhibitor by screening for p21 WAF1/Cip1 -inducing agents, had attractive pharmacodynamic and pharmacokinetic properties (11). OBP-801 exerted the most potent HDAC-inhibitory activity when compared with other HDAC inhibitors (11).…”
Section: Introductionmentioning
confidence: 99%
“…At least 12 different HDACis are currently in use for clinical trials, and more are being sought to augment chemotherapy (4, 5, 7), immunotherapy/ cancer vaccines (14) and overcome multi-drug resistance which are common to diverse cytostatic or receptor-mediated drugs (3,8,9,(36)(37)(38) HDAC inhibitors were first isolated from microorganisms, and continue to be developed from microbial metabolites (39,40). Likewise, endogenous microbial fermentation of nondigestible starches in gut microflora can release HDACi butyrate -believed to prevent colon cancer (31,32).…”
Section: Discussionmentioning
confidence: 99%